2017
DOI: 10.22159/ijap.2017.v9s1.79_86
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Validation of Clopidogrel in Human Plasma Through Ultrahighperformance Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Objective: This study developed a sensitive, selective, and valid method for analyzing clopidogrel in human plasma using liquid chromatographytandem mass spectrometry (LC-MS/MS). Methods:The chromatography separation was performed on the waters ACQUITY UPLC Class BEH C 18 1.7 µm (2.1 × 100 mm) column, consisting of 0.1% formic acid in water and 0.1% formic acid in acetonitrile (30-70) as the mobile phase, and an isocratic elution with a flow rate of 0.2 mL/minutes. The mass detection was performed using a Wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The results of REMO stability tests were summarized in table 6. The findings showed that REMO was durable in rat plasma under various storage conditions studied, including stored at Freeze-thaw at-80 °C, Bench top (normal room temperature) for 48 h, Auto-sampler at 2-8 °C for 24 h and Long term at-80 °C for 30 d [24].…”
Section: Stability Studiesmentioning
confidence: 94%
“…The results of REMO stability tests were summarized in table 6. The findings showed that REMO was durable in rat plasma under various storage conditions studied, including stored at Freeze-thaw at-80 °C, Bench top (normal room temperature) for 48 h, Auto-sampler at 2-8 °C for 24 h and Long term at-80 °C for 30 d [24].…”
Section: Stability Studiesmentioning
confidence: 94%
“…Chromatographic separation is based on the transfer of a liquid (mobile phase) carrying the analytical mixture through a stationary medium. The interaction difference of the analyte with the surface of the medium results in a difference in retention time between the components of the mixture [16][17][18][19][20]. UPLC differs from other chromatographic methods in the size of the column particles is substantially smaller.…”
Section: Chromatography Conditionmentioning
confidence: 99%
“…After examining its effects in more than 30000 patients worldwide, the clinical advantage of long-term clopidogrel treatment in reducing atherothrombotic disorders is demonstrated [10,11]. Reviews of the literature indicate that UV spectrophotometry [12], high-performance liquid chromatography with ultraviolet detection [13], gas chromatography with mass spectrometry [14], and highperformance liquid chromatography with mass spectrometry [15,16] are used to quantitatively analyze clopidogrel in pharmaceutical preparations or biological liquids.…”
Section: Introductionmentioning
confidence: 99%